Qawaid Tafsir dan Ushul Tafsir Siti Aisyah dalam Kitab Sahih Muslim - Nirwana AN, Andri (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2021)
Qawaid Tafsir has a purpose, namely the rules needed by commentators in understanding the verses of the Qur'an. The rules needed by the exegetes in understanding the Qur'an include appreciation of its uslubs, understanding of its origins, mastery of its secrets and linguistic rules. Siti Aisyah's contribution in the Interpretation of the Qur'an has become a reference for many mufassirins, whose interpretation results are written in the books of Hadith, there is even a special section of the Muslim hadith books, namely the chapter on the hadith books of interpretation. How qawaid and ushul interpretation siti aisyah in the book of hadith Sahih Muslim is the goal of solving the problem of this article. The method used in this research is Systematic Literature Review (SLR) which is a systematic way to collect, critically evaluate, integrate and present findings from various research studies on research questions or topics of interest. The SLR provides a way to assess the level of quality of existing evidence on a question or topic of interest. The SLR provides a broader and more accurate level of understanding than traditional literature reviews. The results of this study were found five verses interpreted by Siti Aisyah in the book of Hadith Sahih Muslim. The details of the explanation can be seen in the discussion chapter. This research is useful for developing the results of the interpretation of the Companions in mapping the methodology of interpretation, qawaid Tafsir and Usul Tafsir.ABSTRAKQawaid Tafsir mempunyai maksud ialah kaidah-kaidah yang diperlukan oleh para mufasir dalam memahami ayat-ayat Al-Qur’an. Kaidah-kaidah yang diperlukan para mufasir dalam memahami Al-Qur’an meliputi penghayatan uslub-uslub nya, pemahaman asal-asal nya, penguasaan rahasia-rahasia nya dan qaidah-qaidah kebahasaan. Kontribusi Siti Aisyah dalam Penafsiran Al Qur’an banyak menjadi referensi bagi para mufassirin, yang hasil dari penafsiran nya tersebut tertulis dalam kitab kitab Hadis, bahkan ada bagian khusus dari kitab hadis Muslim yatu bab kitab hadis tafsir. Bagaimana qawaid dan ushul tafsir siti aisyah dalam kitab hadis sahih Muslim menjadi tujuan dari penyelesaian masalah artikel ini. Metode yang digunakan dalam penelitian ini adalah Systematic Literature Review (SLR) adalah cara sistematis untuk mengumpulkan, mengevaluasi secara kritis, mengintegrasikan dan menyajikan temuan dari berbagai studi penelitian pada pertanyaan penelitian atau topik yang menarik. SLR menyediakan cara untuk menilai tingkat kualitas bukti yang ada pada pertanyaan atau topik yang menarik. SLR memberikan tingkat pemahaman yang lebih luas dan lebih akurat daripada tinjauan literatur secara tradisional. Adapun hasil dari penelitian ini adalah ditemukan lima ayat yang ditafsirkan oleh siti aisyah dalam kitab hadis Sahih Muslim. Adapun rincian penjelasan nya bisa melihat pada bab pembahasan. Penelitian ini berguna untuk mengambangkan hasil penafsiran para sahabat dalam pemeteaan metodologi tafsir, qawaid Tafsir dan Ushul tafsir..